Fabrication of micropatterned thin films through controlled phase separation of polystyrene/polydimethylsiloxane blends by spin coating - Agarwal, Swarnima; Lu, Mingyuan; Sarkar, Jayati (Frontiers in Soft Matter, 2023)
In this study, we blended two readily available polymers, polydimethylsiloxane (PDMS), a semi-crystalline polymer and polystyrene, an amorphous polymer, both having widely varying physical properties. The blend is then spin-coated to form a thin film. We investigated the effects of relative polymer concentration, spin coating speed and environmental factors, such as temperature, on the ultimate morphologies of the phaseseparated thin films. It was found that it is possible to regulate the morphologies of the thin films to give desirable microstructures such as spherical droplets, holes, bi-continuous lamellar structures, and tubules by controlling the fabrication conditions. The polymer blend films with higher PS concentrations were shown to form a bilayer system with an upper PSrich layer due to the thermodynamic instability of the film caused by the rapid evaporation of solvent, whereas for higher PDMS concentration, the cohesive forces engender microtubule formation with high surface roughness in such films.